Strategi Mengatasi Distraksi Belajar Siswa Kelas VI Melalui Pendekatan Interpretatif - Kailla Aurelia Putri; Bahrodin, Ariga; Putri, Kailla (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2026)
Distractions in the classroom are one of the obstacles that affect concentration and the active participation of elementary school students in the overall learning process. This study aims to describe the strategies employed by sixth-grade students to cope with classroom at MI Bustanul Ulum Brudu Jombang. This study employs a qualitative methode using a case study design. The subjects of the study are the sixth-grade teachers, the student affairs coordinator and sixth-grade students, with data collection conducted through observation, in-depth interviews and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions using thematic analysis, as well as validity testing through methodological triangulation and source triangulation. The results of this study reveal that students’ strategies for dealing with learning distractions include self-regulation through independent efforts to regain focus, such as controlling attention and increasing learning awareness, as well as utilizing the support of the learning environment. These strategies are also reinforced by the teacher’s role through the use of varied teaching methods and media that help minimize disruptions. Additionally, students’ experiences in dealing with distractions foster metacognitive awareness, enhance internal motivation and promote independent learning. Therefore, distractions during learning are not only obstacles but also play a role in helping students develop more effective self-regulations skills.